Cerebral palsy : early diagnosis, intervention and risk factors - Naletilić, Mladenka (Array, 2009)
Summary: Early diagnosis and intervention intensity were suggested to be crucial factor in cerebral palsy (CP) treatment. Herein we observed 347 children diagnosed for CP in Clinical Hospital Mostar, Bosnia and Herzegovina, and studied the relationship between (a) intervention start point and the final motor outcome, (b) intensity of treatment and final outcome, and (c) relationship between documented risk factors and early diagnosis of the CP. Our study suggests that it is possible to relatively accurately diagnose the CP in the first trimester. Previous miscarriages, sepsis and intracerebral haemorrhage were significantly related to early diagnosis, while delivery outcome, RDS, premature birth, intracerebral haemorrhage, sepsis, meningitis, hydrocephalus and convulsions were found as significantly related to final motor CP outcome. We have found no significant influence of the intervention intensity and final diagnosis. Our results support the idea that the intervention start point has to be considered as one of the most important factors for the effective intervention program. In future studies dealing with the CP interventions and risk factors, special attention should be paid to homogeneity and size of the sample, as well as necessity of including the non-treated controls in the investigation